Love and other conspiracies - Marlowe, Mallory (Berkley Romance, 2024)
"Hallie Barrett's life has imploded after she's dumped by her hotshot ex, who also happens to be her coworker and the star of the online series she was producing. Without a new show to present for the company competition, she'll be out of a job. But inspiration can come from the strangest places . . . like the hottest guy she's ever seen passionately discussing Bigfoot on a late-night docuseries. Hayden Hargrove made a name for himself as a cryptid expert on his hit podcast, and he is intrigued by the plucky, blue-haired producer who offers him the opportunity to lead his own web show. When the production team sees that Hayden's solo on-screen presence is bad enough to make a ghost blanch, Hallie jumps on camera too, hitting him (and his cryptids) with a healthy dose of skepticism-and enough chemistry to electrify their show to the top of the competition. As Hayden and Hallie investigate the unknown, they unearth feelings for each other that shake their beliefs to the core. In their search for Mothman, aliens, and the truth, the most elusive discovery might just be learning to love again"--